Influence of life‐style factors, including second‐hand smoke, on dental caries among 3‐year‐old children in Wuxi, China. (13th August 2019) - Tang, Shai‐Di; Zhang, Yan‐Xiao; Chen, Li‐Mei; Wang, Yue‐Yan; Cheng, Yang; Tang, Li‐Qin
Abstract : Aim: To examine the association of life‐style factors, including second‐hand smoke, with dental caries among 3‐year‐old children in Wuxi, China. Methods: A multi‐stage stratified random cluster sampling method was used, and 283 children were recruited. The prevalence of dental caries was 29.3% (83/283). Results: Univariate analysis indicated that the possible related factors of dental caries included sleep duration, interest in snacks, candy, exposure to second‐hand smoke and weight of birth (all P  < 0.05). Meanwhile, multivariate logistic regression analysis suggested that children who had used fluoride were less susceptible to dental caries than those who had not used fluoride before ( P  < 0.05). Moreover, the risk of dental caries in children who were very interested in snacks was greater than those with little interest in snacks ( P  < 0.05). Conclusions: Life‐style behaviours are crucial factors and should attract enough attention. There might be a potential negative effect of second‐hand smoke on the deciduous caries, but it still requires further studies. A co‐ordinated effort by health‐care providers, policymakers and health institutions has successfully improved children's oral health and the awareness of hygiene knowledge among citizens in Wuxi city.